2022
DOI: 10.1021/acs.macromol.1c02242
|View full text |Cite
|
Sign up to set email alerts
|

Stress-Dependent Multicolor Mechanochromism in Epoxy Thermosets Based on Rhodamine and Diaminodiphenylmethane Mechanophores

Abstract: Mechanochromic polymers exhibit potential applications in damage reporting and stress sensing. Despite the rapid progress achieved in recent years, mechanochromic structural polymers, such as epoxy thermosets, remain difficult to develop, let alone structural materials that can distinguish different levels of stress by a visual color change. This work presents a new class of multicolor mechanochromic epoxy thermosets that can discriminate between low and high compressive stresses via the incorporation of two d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 59 publications
3
13
0
Order By: Relevance
“…As shown in Figure 2c, the intensity of the Rh absorption band became more pronounced ratiometrically with increasing compressive stress, which is consistent with a previous study. 12 Alternatively, the amount of force-activated DS moiety increased with stress rapidly and plateaued at ~1.5 GPa for both EP-DS 3.5 and EP-DS 0.35 . Otsuka et al also reported a similar plateau in the dissociation ratio of diarylbibenzofuranone (DABBF) due to the high mechanosensitivity of DABBF in star-shaped polystyrene in contrast to DABBT in linear polystyrene upon grinding.…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…As shown in Figure 2c, the intensity of the Rh absorption band became more pronounced ratiometrically with increasing compressive stress, which is consistent with a previous study. 12 Alternatively, the amount of force-activated DS moiety increased with stress rapidly and plateaued at ~1.5 GPa for both EP-DS 3.5 and EP-DS 0.35 . Otsuka et al also reported a similar plateau in the dissociation ratio of diarylbibenzofuranone (DABBF) due to the high mechanosensitivity of DABBF in star-shaped polystyrene in contrast to DABBT in linear polystyrene upon grinding.…”
Section: Resultsmentioning
confidence: 95%
“…Epoxy thermosets with covalently linked Rh and DS mechanochromophores were prepared by a facile strategy, as shown in Figure 1. The Rh-functionalized epoxy prepolymer DGEBA-Rh was prepared via the condensation reaction of Rh-NH 2 (4.5 mol%) with excess DGEBA at 150 C for 3 h. 12 The mixtures of DGEBA-Rh, curing agents DS-NH 2 and 2,2 0 -(ethylenedioxy)bis(ethylamine) (EDR-148), in a stoichiometric epoxide-amine ratio, were fully cured by sequential curing procedures (80 C for 8 h and 150 C for 4 h). A series of epoxy thermosets with varying Rh:DS molar ratios were obtained (Table S1); the samples are referred to as EP-Rh 4.5 -DS y , where y represents the molar percentage ratio of the DS moiety relative to the epoxy resin.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations